Non-coding RNAs and exosomal non-coding RNAs in lung cancer: insights into their functions - Lv, Xiaolong; Yang, Lei; Xie, Yunbo; Momeni, Mohammad Reza (Frontiers in Cell and Developmental Biology, 2024)
Lung cancer is the second most common form of cancer worldwide Research points to the pivotal role of non-coding RNAs (ncRNAs) in controlling and managing the pathology by controlling essential pathways. ncRNAs have all been identified as being either up- or downregulated among individuals suffering from lung cancer thus hinting that they may play a role in either promoting or suppressing the spread of the disease. Several ncRNAs could be effective non-invasive biomarkers to diagnose or even serve as effective treatment options for those with lung cancer, and several molecules have emerged as potential targets of interest. Given that ncRNAs are contained in exosomes and are implicated in the development and progression of the malady. Herein, we have summarized the role of ncRNAs in lung cancer. Moreover, we highlight the role of exosomal ncRNAs in lung cancer.